A novel approach to alpha-lipoic acid therapy in the treatment of diabetic peripheral neuropathy - Sementina, Alicja; Cierzniakowski, Mateusz; Rogalska, Julia; Piechowiak, Izabela; Spichalski, Marek; Araszkiewicz, Aleksandra (Journal of Medical Science, 2022)
Diabetic peripheral neuropathy (DPN) is a heterogenic disorder prevalent amongst patients suffering from diabetes mellitus (DM), with symptoms comprising neuropathic pain, paresthesia, and numbness in distal lower limbs. Alpha-lipoic acid (ALA) is proposed as a pathogenesis-oriented treatment option, targeting underlying causes of neural lesions such as hyperglycemia, metabolic and microvascular dysfunctions, and cellular oxidative stress. We performed a comprehensive review of controlled clinical trials demonstrating the clinical usefulness of ALA in the treatment of DPN, published in the last 5 years to determine the benefits of ALA monotherapy and combined treatments with other known antioxidants. We also investigated the differential efficacy of oral versus intravenous ALA administration. Clinical trials show the efficacy of ALA treatment, attributed to its anti-inflammatory, anti-hyperglycemic, and antioxidant properties, as well as its function in the endothelial activation and lipid metabolism parameters. ALA supplementation is associated with amelioration in nerve conduction velocity scores, clinically significant reduction of reported neuropathic pain, burning and paresthesia, as well as a decrease in serum triglycerides, improved insulin sensitivity, and quality of life.